Verified and validated design curves and strength reduction factors for post-tensioned composite steel-timber stiffened wall systems. (1st February 2020) - Orlowski, Kristopher
Highlights: Novel Post-tensioned Composite Steel-Timber (PT-CST) stiffened wall systems explored. PT-CST performance investigation through analytical, experimental and FE means. Developed design curves and simple design method including a strength reduction factor due to PT. Parameters: PT force, panel thickness, number of stiffeners, wall height and load. Input capacity, output optimal configuration. Input configuration, output load and PT. Abstract: Viability of timber-based solutions for projects is often limited by lengthy modelling and preliminary design when compared to traditional systems such as precast concrete. However, sustainability principles are becoming more prevalent in construction with increasing demands for mid-rise buildings constructed through automated prefabrication via Design for Manufacturing and Assembly (DfMA) techniques. Considering this, this paper introduces and presents design curves for Post-Tensioned (PT) Composite Steel-Timber stiffened wall systems under axial loading. Notably material efficient, they consist of a stiffened engineered timber panel, having half the typical minimum thickness of Cross-Laminated Timber (CLT). Composite action is gained through integrally stiffening the panel with timber studs and steel Square Hollow Sections (SHS), which house a PT rod. The post-tensioning facilitates vertical panel to panel connections for quick on-site assembly, permanent tie-down and self-centering rocking mechanism functionality. A full-scale experimental testing program was conducted in conjunction with analytically verified and validated finite element models. Parametric changes include: level of post-tensioning, number of stiffeners, thickness of panel, height of the wall and applied load. Highly versatile yet simple design curves have been developed from an exhaustive set of incremental results. In addition, a strength reduction factor capturing the effects caused by post-tensioning is proposed. With these, a simple design procedure has been outlined for quick feasibility analysis and preliminary design. That is, for a desired load capacity and level of post-tensioning, the optimal system configurations is given. Likewise, for a chosen configuration and level of post-tensioning the allowable axial load is given.